Pengaruh Gelombang Dan Kemiringan Pantai Terhadap Perubahan Morfologi Pantai Bergambut - Yosafat Sijabat; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Bengkalis Island is a peat island which is prone to beach abrasion. Abrasion happens at the rate of 32,5 m/year,especially on the west of Bengkalis Island. The relatively lightweight characteristic of peat materials makes it moresusceptible to beach abrasion and sedimentation. Since peatland beaches are very rare in the world, study aboutpeatland beaches abrasion was also rarely done. To understand this phenomenon, this study has made a physicalmodel in the laboratorium. Experiment using this physical model was done in Hydrotechnical Laboratorium atDepartment of Civil Engineering, Universitas Riau, through Multi Teaching Flame method, while the sample materialof peat soil from Bengkalis Island Beach was subjected into preliminary property test. Experiment was done using 3scenarios of wave height generated by wave generator, and 3 variation of beach slope, which was 1:2.5, 1:5 and1:7.5. Data taken on this study were elevation of peak and valley of the wave (H), wave period (T) and sedimentheight (d) which was measured every 30 minutes for 300 minutes. Morphological changes of beach as a result ofbeach abrasion and sedimentation are further evaluated in terms of wave height and beach slope. Through this study,it can be concluded that wave length and rate affected by depth of the sea. The smaller the slope of the beach, themore stable the beach, which make it more susceptible from erosion.Keyword: Bengkalis Island, Morphological Changes, Physical Model, Wave and Slope